CRISPR-Cas9-based genome editing of banana - Tripathi, L.; Ntui, V.O.; Tripathi, J.N. (Springer, 2020)
Genome editing is an emerging powerful new breeding tool, which can be applied for genetic improvement of banana for important agronomic traits such as resistance to biotic stresses, adaptation to climate change, and high yielding. Banana is an important staple food and cash crop, feeding millions of people in tropical and subtropical countries. Recently, CRISPR-Cas9-based genome editing system has been established for banana in a few laboratories. Here, we describe the procedures for generation of genome-edited events of banana, detection of targeted and potential off-target mutations, and phenotyping for important traits such as disease resistance. This chapter will provide readers strategy for applying CRISPR-Cas9-based genome editing for improvement of banana.